2017
DOI: 10.1080/02713683.2016.1255335
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Purtscher’s Retinopathy Treatments: A Systematic Review

Abstract: Both treatment and no treatment improve vision in Purtscher's retinopathy patients, but the difference between no treatment and glucocorticoid therapy had no statistical significance. The evidence quality for this conclusion was "very low" and had large bias. Further research is required to understand the safety of Purtscher's retinopathy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…Current treatments include glucocorticoid therapy, traditional Chinese medicine, and glucocorticoid integrative medicine therapy. A systematic review found that the difference between no treatment and glucocorticoid therapy showed no statistical significance [9]. In the present case, Purtscher's or Purtscher's-like retinopathy did not involve the macula of both eyes.…”
Section: Discussioncontrasting
confidence: 65%
“…Current treatments include glucocorticoid therapy, traditional Chinese medicine, and glucocorticoid integrative medicine therapy. A systematic review found that the difference between no treatment and glucocorticoid therapy showed no statistical significance [9]. In the present case, Purtscher's or Purtscher's-like retinopathy did not involve the macula of both eyes.…”
Section: Discussioncontrasting
confidence: 65%
“…Although it was reported that the difference between no treatment and glucocorticoid therapy had no statistical signi cance, the evidence quality for this conclusion was "very low" and had large bias [4] . Therefore, if possible, a further large-scale prospective study on these cases is necessary.…”
Section: Discussionmentioning
confidence: 93%
“…In literature, there have been case reports regarding the use of corticosteroid. There is no definitive guideline for the treatment of these cases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%